(untitled) (Sociología y tecnociencia, 2022)
One need only think of areas such as information technology, telecommunications, nanotechnology, biotechnology, robotics or so‐called artificial intelligence, among others, to identify the indisputable fact that in recent decades there have been enormous scientific and technical advances, linked to increased labour productivity. Without looking at the social reality, it might be thought that, "as a consequence", the living conditions of the world’s population as a whole have improved considerably.